Role of micronutrients against downy mildew of pearl millet caused by Sclerospora graminicola (Sacc.) Schroet - ANIL KUMAR, POOJA SANGWAN*, KUSHAL RAJ and (Indian Phytopathology, 2016)
Downy mildew of pearl millet incited by Sclerospora graminicola (Sacc.) Schroet is the most widespread and destructive disease of pearl millet in India and other pearl millet growing area of the world. Micronutrients play an important role in plant metabolism by affecting the phenolics and lignin content and also membrane stability. In present study the experiment was conducted in sick plot of Department of Plant Pathology research area of CCS Haryana Agricultural University Hisar by soil application of molybdenum through Ammonium molybdate, copper in the form of copper sulphate, boron in the form of sodium tetraborate and their combinations molybdenum + copper, molybdenum + boron, copper + boron, molybdenum + boron + copper at the time of sowing of pearl millet. Observations on germination percentage, per cent disease incidence at 30 and 60 days after sowing and yield data on harvest were recorded. Downy mildew incidence was minimum (0.0 % at 30 DAS), (4.6% at 60 DAS) in treatment of soil application of molybdenum @ 500 g/acre + boron @ 4 kg/acre + Copper @ 8 kg /acre. Maximum germination (%) was observed in treatment with molybdenum (60.4%) followed by molybdenum + boron (58.0%). Grain yield was maximum (1244.4 kg/ha) in treatment receiving soil application of molybdenum @ 500 g/acre in comparison to control (1100 kg/ha).